Synthesis of tetrahydropyrans from sugar lactones - Estevez, J; Fairbanks, A; Fleet, G (1998)
Dehydration of both γ- and δ- hexonolactones, either by intramolecular nucleophilic displacement of triflate leaving groups at C-2, or by Mitsunobu type displacement of the OH-6, provides access to bicyclic lactones which contain tetrahydropyran rings. Reduction or nucleophilic ring opening of these bicyclic lactones furnishes polyfunctionalised tetrahydropyrans in good yield.